Metrologically based procedures for the temperature, heat and heat flow rate calibration of DSC - Sarge, Stefan M.; Hemminger, W.; Gmelin, E.; Höhne, G. W. H.; Cammenga, H. K.; Eysel, Walter (Journal of thermal analysis and calorimetry, 1997)
Metrologically based measuring procedures and evaluation methods are recommended as guidance for practical temperature, heat and heat flow rate calibration of DSC instruments which are largely independent of instrumental, test and sample parameters. The relevant terms are defined, the measuring procedures and evaluation methods described, calibration materials and their characteristic data stated and guidance for the sample handling provided. Reference is made to three extended papers on calibration. The recommendations were developed by the working group ‘Calibration of Scanning Calorimeters’ of the German Society of Thermal Analysis (GEFTA).